Role of Internet of Things in the Smart Grid Technology - Al-Ali, Abdulrahman (2015)
Internet of Things (I.o.T) is a recently emerged as enabling technology for the smart gird, smart health, smart transportation and smart environment .The smart grid applications such smart home automations, Intelligent Electronic Device (IED) and Distributed Energy Resources (DER) are major I.o.T objects that can be addressable using the IPV6. These objects are called the smart grid internet of things (SG-I.o.T). The SG-I.o.T generates big data that requires high speed computing infrastructure, widespread computer networks, big data storage, software, and platforms services. Utility companies’ control and data centers cannot handle such a large number of devices, high speed processing and massive data storage. Building large data center’s infrastructure takes a long time, requires widespread communication networks and huge capital investment. In addition, the center must have tailored operation and maintenance software packages such as distribution management system (DMS), geographic information systems (GIS), outage management systems (OMS), customer information systems (CIS) and supervisory control and data acquisition system (SCADA). Maintaining and upgrading control and data centers’ infrastructure and communication networks as well as updating and renewing software package licenses requires additional cost. An emerging computing paradigms such as cloud computing can be used as a smart grid enabler to replace the legacy utilities data centers. As best described by the NIST, “Cloud computing is a model for enabling convenient, on-demand network access to a shared pool of configurable computing resources (e.g., networks, servers, storage, applications, and services) that can be rapidly provisioned and released with minimal management effort or service provider interaction.” The talk will highlight the role of I.o.T and cloud computing services and development models in the smart grid. Mapping the smart grid NIST existing seven domain conceptual models with the cloud computing NIST service models will also be explored.